Reactive sulfur species inhibit the migration of PDGF-treated vascular smooth muscle cells by blocking the reactive oxygen species-regulated Akt signaling pathway. (1st February 2021) - Ishii, Shunichi; Ashino, Takashi; Fujimori, Hiroki; Numazawa, Satoshi
Abstract: Vascular smooth muscle cell (VSMC) migration contributes to vascular remodeling after injury, whereas oxidative stress generated through dysfunctional redox homeostasis induces hypermigration, leading to arteriosclerosis. Platelet-derived growth factor (PDGF)-induced reactive oxygen species (ROS) serve as intracellular signaling molecules in VSMCs. Reactive sulfur species (RSS) may serve as a biological defense system because of the antioxidative properties of highly nucleophilic sulfane sulfur. However, insufficient information is available on its function in PDGF-induced VSMC migration. Here we show that PDGF significantly increased the levels of intracellular sulfane sulfur and that intracellular sulfane sulfur donors, donor 5a and Na2 S4, inhibited the increase in ROS levels in PDGF-treated VSMCs and inhibited their migration. Consistent with the migration results, sulfane sulfur donors inhibited Akt phosphorylation, a downstream signaling molecule in the PDGF cascade, without affecting the autophosphorylation of PDGF receptor-β. Further, sulfane sulfur donors inhibited vinculin and paxillin recruitment to the leading edge of VSMCs in response to PDGF to decrease focal adhesion formation. These findings suggest that RSS are required for PDGF-stimulated VSMC migration through the regulation of the ROS-regulated Akt pathway, which may contribute to focal adhesion formation. Our findings provide insight into RSS as novel regulators of vascular redox homeostasis.